2012
DOI: 10.4236/jwarp.2012.49082
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Variations in Water Quality of the Chao Phraya River, Thailand, between 1991 and 2008

Abstract: Spatio-temporal variations in the water quality of the Chao Phraya River, Thailand, were examined, on average-yearly basis, between 1999 and 2008, from 32 surface water stations from the river origin to the delta. Five water quality parameters viz., DO, BOD, TCB, FCB, NH3-N and water temperature were used in the analysis. Analysis was performed by using the Self Organizing Maps. Four distinct spatially approached clusters were classified, according to the similarity of water quality parameters, while temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Many WQIs are potentially useful in the planning of water resource protection, improvement, and utilization, whereas some WQIs have been specifically developed to aid in environmental planning and decision making. Several authors have shown that multivariate statistical approaches are more appropriate to understand the underpinning patterns of water quality parameters, especially due to their interdependence (e.g., Sheela et al, 2012;Avakul and Jutagate 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many WQIs are potentially useful in the planning of water resource protection, improvement, and utilization, whereas some WQIs have been specifically developed to aid in environmental planning and decision making. Several authors have shown that multivariate statistical approaches are more appropriate to understand the underpinning patterns of water quality parameters, especially due to their interdependence (e.g., Sheela et al, 2012;Avakul and Jutagate 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many studies and literature reviews have been carried out on climate change phenomena and sustainable urban water supply, at local and global scales, outlining the problems associated with climate change impacts and uncontrolled urbanization [ 5 , 10 , 48 , 49 ]. The mitigation of the effects of climate change requires a collection of reliable data on water quality for effective monitoring and management at local, regional, and global levels as previously performed in several countries [ 48 , 49 , 52 , 53 , 54 ]. However, a gap remains on the longitudinal profiling of water quality assessment across the different climatic regions.…”
Section: Introductionmentioning
confidence: 99%